PROBLEM TATA KELOLA PEMERINTAHAN YANG BERBASIS WILAYAH KEPULAUAN DI PROVINSI MALUKU UTARA - Jamal Hi Arsyad; Bambang Daud (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Indonesia is the largest archipelago in the world, which has various natural resources, especially in the marine and fisheries aspects. In the context of North Maluku which has such great potential and has an important meaning not only at the regional economic level but also at the national economy, it is necessary to have synergy between the Regional and Central Governments in planning and managing the various potentials that exist as a basic need. However, in practice the regional government experiences various problems, especially in the aspect of governance based on the archipelago in North Maluku. The results of this research indicate that there are regulations or various policies needed to answer these various problems, especially the utilization of various potentials for the prosperity and welfare, especially the people of North Maluku. Thus, strengthening governance is a must.